2015
DOI: 10.1111/ajt.13413
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Uncertainty and Fallbacks Can Increase the Number of Transplants in a Kidney-Paired Donation Program

Abstract: A kidney paired donation (KPD) pool consists of transplant candidates and their incompatible donors along with non-directed donors (NDDs). In a match run, exchanges are arranged among pairs in the pool via cycles, as well as chains created from NDDs. A problem of importance is how to arrange cycles and chains to optimize the number of transplants. We outline and examine, through example and by simulation, four schemes for selecting potential matches in a realistic model of a KPD system; our proposed schemes ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…A use of the calculator that first motivated our investigations arises in the context of allocations in a KPD program where algorithms are developed to optimize the number of transplants or some other measure of utility (31)(32)(33)(34). An alternative approach defines the value of a potential transplant from a given donor to a given recipient as the estimated probability that the graft would survive for 5 (or 10) years.…”
Section: Discussionmentioning
confidence: 99%
“…A use of the calculator that first motivated our investigations arises in the context of allocations in a KPD program where algorithms are developed to optimize the number of transplants or some other measure of utility (31)(32)(33)(34). An alternative approach defines the value of a potential transplant from a given donor to a given recipient as the estimated probability that the graft would survive for 5 (or 10) years.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper (Fumo et al 2015) expands on this issue in the context of the experience of the APD, and other papers (Bray et al 2015; Li et al 2014) on matching strategies have found that using shorter chain segments is as efficient as long chains, even in the context of the usual match run approach.…”
Section: Discussionmentioning
confidence: 99%
“…A useful extension of the proposed utility-based method is to incorporate cycles into the lookahead multiple decision strategy. In most current implementations, disjoint chains and cycles are selected to optimize the total expected utility by solving an integer programming problem in each match run (Ashlagi et al 2011; Bray et al 2015; Li et al 2014). Another approach would be to alternate between chains and cycles in match runs, using look-ahead strategies for the chains and traditional optimization approaches for the cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant centers upload data on the donor and the intended recipient into a centralized computer system run by the consortia including detailed HLA information, renal anatomy, and renal function. As new pairs are added, the matching algorithm is rerun, facilitating the greatest number of transplants …”
Section: Kidney Paired Exchange Backgroundmentioning
confidence: 99%